Buccoadhesive Tablets of Losartan Potassium: Design and Characterization - Pande, Saikat (International Journal of Pharmaceutical & Biological Archive, 2010)
Adhesive buccal tablets of losartan potassium were prepared with an objective to increase the bioavailability by avoiding first pass metabolism and also to prolong the drug release. Carbopol 934P was used as a primary mucoadhesive polymer and either sodium CMC, HPMC K4M or sodium alginate as secondary polymer, in different ratios. The buccal tablets were subjected for evaluation of various physicochemical properties such as weight variation, tablet thickness, content uniformity, surface pH, bioadhesive strength and swelling index. In vitro drug release studies were carried out using flow thru cell. Chicken pouch was used as model mucosa membrane in in vitro permeation study. Stability studies were carried out at refrigerator (2-8°C), room temperature (25-30°C) and accelerated temperature (45-50°C) for two months. The results of weight variation, thickness, content uniformity, surface pH and bioadhesive strength of all batches were satisfactory and comply with theoretically expected values. In vitro release studies demonstrate a highest percentage of drug release from the group III formulations (sodium alginate as a secondary polymer). However formulation of this group showed fast fragmentation and higher matrix erosion. Formulation of group I (sodium carboxymethyl cellulose as secondary polymer) and group II (HPMC K4M as secondary polymer) showed an adequate release and mucoadhesion. In vitro drug release follows zero order kinetics for all the formulations. In vitro permeation studies further confirm the prolonged release as well as transport of drug molecule across a biological membrane. Stability studies indicate no significant changes with respect to surface pH, bioadhesive strength and drug content at the end of two months.